2021
DOI: 10.1186/s12967-021-03173-x
|View full text |Cite
|
Sign up to set email alerts
|

TRIM38 triggers the ubiquitination and degradation of glucose transporter type 1 (GLUT1) to restrict tumor progression in bladder cancer

Abstract: Background Loss-of-function mutations or abnormal expressions of E ubiquitin ligases contributes to tumorigenesis. TRIM38 was reported to regulate immunity, inflammatory responses or apoptosis, but its roles in tumor progression remain inconclusive. This study aimed to investigate the functional roles of TRIM38 in bladder cancer to identify effective targets. Methods Firstly, the expression data of ubiquitination-associated genes were derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…In our cohort, GLUT1 expression was not limited to the hypoxic regions of the tissue samples, being equally present in the membranes of UBC cells located near to patent and mature blood vessels. In accordance with this, other studies have described positive [lysine deacetylase SIRT1 [53]] or negative [microRNA-218 [54], E3 ubiquitin-protein ligase TRIM38 [55]] regulators of GLUT1 expression in BC other than hypoxia. Nevertheless, the GLUT1 expression by the normoxic and/or hypoxic UBC cells showed a clear association with the aggressiveness parameters in our study, but no correlation with the survival rates was reached.…”
Section: Discussionsupporting
confidence: 76%
“…In our cohort, GLUT1 expression was not limited to the hypoxic regions of the tissue samples, being equally present in the membranes of UBC cells located near to patent and mature blood vessels. In accordance with this, other studies have described positive [lysine deacetylase SIRT1 [53]] or negative [microRNA-218 [54], E3 ubiquitin-protein ligase TRIM38 [55]] regulators of GLUT1 expression in BC other than hypoxia. Nevertheless, the GLUT1 expression by the normoxic and/or hypoxic UBC cells showed a clear association with the aggressiveness parameters in our study, but no correlation with the survival rates was reached.…”
Section: Discussionsupporting
confidence: 76%
“…Additionally, the expression of SLC2A1 is significantly upregulated in higher pathologic stages in various cancers. Previous studies have reported that SLC2A1 is highly expressed in a variety of cancers, such as BLCA, LUAD, LIHC, CESC, COAD, OV, UCEC, BRCA, STAD, ESCA, and PAAD [ 11 , 12 , 13 , 14 , 15 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. These results are consistent with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…He et al found that GSDMB could bind to STAT 3, thereby activating STAT 3 signaling in bladder cancer, and demonstrated that GSDM could interact with USP 24B to hinder the degradation of GSDMB in bladder cancer, thus the USP 24/GSDMB/STAT 3 axis could be a new signaling pathway for targeted bladder cancer therapy ( 29 ). Wang et al demonstrated that TRIM 38 plays an inhibitory role in the development of bladder cancer, and the TRIM 38/GLUT 1 axis is of great importance as a weak point for bladder cancer treatment ( 30 ). The relationship between the remaining three predictors and bladder cancer is not yet supported by relevant experimental evidence and literature; therefore, they may provide options for later investigators when studying potential therapeutic targets for bladder cancer.…”
Section: Discussionmentioning
confidence: 99%